2018
DOI: 10.1186/s12958-018-0332-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactate promotes specific differentiation in bovine granulosa cells depending on lactate uptake thus mimicking an early post-LH stage

Abstract: BackgroundThe LH-induced folliculo-luteal transformation is connected with alterations of the gene expression profile in cells of the granulosa layer. It has been described that hypoxic conditions occur during luteinization, thus favoring the formation of L-lactate within the follicle. Despite being a product of anaerobic respiration, L-lactate has been shown to act as a signaling molecule affecting gene expression in neuronal cells. During the present study, we tested the hypothesis that L-lactate may influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…These findings were further strengthened by the identification of increased glucose consumption and lactate accumulation in post hCG murine follicles ( Harris et al, 2007 ). Recently, it was shown that even under normoxic conditions lactate can act as an effective signaling molecule that induces granulosa cell differentiation ( Baufeld and Vanselow, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings were further strengthened by the identification of increased glucose consumption and lactate accumulation in post hCG murine follicles ( Harris et al, 2007 ). Recently, it was shown that even under normoxic conditions lactate can act as an effective signaling molecule that induces granulosa cell differentiation ( Baufeld and Vanselow, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous testing, cryopreservation does not affect the GC phenotype or steroid production in culture. Also, the abundance of marker transcripts in cultured cells did not reveal significant differences comparing samples prepared from freshly isolated cells with those previously subjected to cryopreservation 16 .…”
Section: Discussionmentioning
confidence: 82%
“…Two-tailed Student's t -test, the p -values are included. This figure is reproduced from Baufeld and Vanselow 16 . Please click here to view a larger version of this figure.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Later, cDNA was synthesized using the SensiFAST cDNASynthesis Kit (Bioline, Luckenwalde, Germany) from 200 ng RNA as done previously (23). The RT-qPCR was executed for gene expression analysis, using SensiFAST SYBR No-ROX (Bioline) with gene-specific primers ( Supplementary Table 3) in a Light Cycler 96 instrument (Roche, Mannheim, Germany) (24).…”
Section: Rna Isolation Cdna Synthesis and Real Time-quantitative Pcmentioning
confidence: 99%